The potential of farm-level technologies and practices to contribute to reducing consumer exposure to aflatoxins: A theory of change analysis - Johnson, Nancy L.; Atherstone, Christine; Grace, Delia (International Food Policy Research Institute, 2015)
This paper describes and assesses the strength of a theory of change for how adoption of farm-level technologies and practices for aflatoxin mitigation can contribute to reductions in aflatoxin exposure among consumers in a market context. In response to widespread concerns about the public health consequences of aflatoxin exposure and its implications for agricultural development and trade, risk-mitigating agricultural technologies and practices are being developed and adapted for developing-country contexts. While some of the technologies have been shown to be effective in reducing on-farm aflatoxin contamination, links between technology adoption and reduced aflatoxin exposure among consumers have not been clearly described. Often, a win-win situation is assumed, although the pathways by which adoption of improved practices by farmers contribute to reduced exposure among consumers are complex and gendered. There any many underlying assumptions, especially about market incentives, consumer behavior, and the feasibility and cost-effectiveness of regulatory approaches in domestic markets in developing countries. Based on the analysis, priority areas for research and development, in particular in CGIAR, are identified.